The Government of Things : Foucault and the New Materialisms - Lemke, Thomas (Book collections on Project MUSE., 2021)
"Critically engaging with some limitations of new materialist scholarship, Lemke draws on Foucault's concept of a "government of things" to propose a relational understanding of political ontologies"--